TTT diagrams and quenching precipitation behavior of 7A36 aluminum alloy extruded plate - LIU Jia; MA Zhimin; LIU Shengdan; DENG Yunlai; ZHANG Xinming (Cailiao gongcheng, 2023)
The time-temperature-transformation (TTT) diagrams of 7A36 aluminum alloy extruded plate were determined by an interrupted-quench method. The quenching precipitation behavior was investigated by calculate phase diagram(CALPHAD) combined with optical microscopy(OM), scanning electron microscopy(SEM), transmission electron microscopy(TEM), scanning transmission electron microscopy(STEM) and high-resolution transmission electron microscopy(HRTEM). The results show that the critical quenching rate for inhibiting the phase transition of 7A36 aluminum alloy by 0.5% is about 15.7 ℃/s. Based on 10%TTT diagram, the nose temperature is determined to be about 338 ℃ with the transformation time of about 22 s. The precipitation of η(MgZn2), T(Al2Zn3Mg3), S(Al2CuMg) or Cu-Zn rich Y phases can be found depending on different isothermal holding temperatures and time, and the precipitation behavior is described in the TTT curve, which is described as a time-temperature-precipitation diagram.η equilibrium phase tends to occur at grain boundary(GB) first and then at sub-grain boundary(SGB) and on dispersoids in the interior of grains, at higher isothermal holding temperature, the size of η phase is larger. The electrical conductivity increases first and then decreases with the increase of holding temperature; isothermal holding at 420 ℃, the increase of electrical conductivity is caused by precipitation of η phase and T phase, while at 330 ℃ and 240 ℃, the increase of electrical conductivity is due to the precipitation of η phase, T phase, S phase and Y phase.